IMPLEMENTASI BLUE OCEAN STRATEGY DI INDONESIA - Yustina Chrismardani (Trunojoyo University of Madura, 2010)
Blue Ocean Strategy was a strategy to create uncontested market and make competition irrelevant. In blue ocean, demand is created rather than fought over. Canvas strategy and value curve was needed to create Blue Ocean Strategy. Its a dinamic process to create a blue ocean, and always needed to check on value curve, in order to find know the time to create another blue ocean. Altough a wellknown strategy, the implementation in Indonesia still rare and needed a manager with a long-term perspective and knowldge to execute this strategy.